Innovating Technology-Enhanced Interventions for Youth Suicide: Insights for Measuring Implementation Outcomes - Szlyk, Hannah S.; Tan, Jia; Lengnick-Hall, Rebecca (Frontiers in Psychology, 2021)
Technology is one medium to increase youth engagement, especially among underserved and minority groups, in suicide preventive interventions. Technology can be used to supplement or adjunct an in-person intervention, guide an in-person intervention, or be the stand-alone (automated) component of the intervention. This range in technological use is now called the continuum of behavioral intervention technologies (BITs). Overall, suicide intervention researchers do not use this terminology to categorize how the role of technology differs across technology-enhanced youth interventions. There is growing recognition that technology-enhanced interventions will not create substantial public health impact without an understanding of the individual (youth, families, and providers), mezzo (clinics and health systems of care), and contextual factors (society, culture, community) that are associated with their implementation. Implementation science is the study of methods to promote uptake of evidence-based practices and policies into the broader health care system. In this review, we incorporate work from implementation science and BIT implementation to illustrate how the study of technology-enhanced interventions for youth suicide can be advanced by specifying the role of technology and measuring implementation outcomes.